Pengaruh Current Ratio, Debt To Equity Ratio, Debt To Asset Ratio, Dan Risk Based Capital Terhadap Profitabilitas Perusahaan Asuransi Di Bursa Efek Indonesia - Ahmad Zulkifli; Dian Ayu Andriani (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aimed to determine the partial and simultaneous effect of the Current Ratio (CR), Debt-to-Equity Ratio (DER), Debt-to-Asset Ratio (DAR), and Risk-Based Capital (RBC) on profitability in insurance companies listed on the Indonesia Stock Exchange during the 2021-2024 period. This study employed a quantitative approach with a descriptive nature. The data collection included 18 insurance companies listed on the Indonesia Stock Exchange. The study period was 2021-2024. The sampling technique used purposive sampling, resulting in 40 observations from 10 companies over four years. Data were collected using secondary data and desk research. This study employed multiple linear regression analysis to analyze the data. The partial results showed that CR, DER, and DAR had no significant effect on profitability, while RBC had a significant effect. Simultaneously, the results showed that CR, DER, DAR, and RBC had a significant effect on profitability in insurance companies listed on the Indonesia Stock Exchange